STAQ: A route toward low power, Multicolor nanoscopy. Issue 5 (12th March 2015) - Rosales, Tilman; Sackett, Dan L.; Xu, Jianhua; Shi, Zhen‐Dan; Xu, Biying; Li, Haitao; Kaur, Gurpreet; Frohart, Erin; Shenoy, Nalini; Cheal, Sarah M.; Wu, Haitao; Dulcey, Andrés E.; et al.
ABSTRACT: Nanoscopy has now become a real procedure in fluorescence microscopy of living cells. The STED/RESOLFT family of nanoscopy approaches has the best prospects for delivering high speed imaging, but the history of STED includes a continuing struggle to reduce the deactivation power applied, along with difficulties in achieving simultaneous multicolor images. In this manuscript, we present a concept for a similar real‐time nanoscopy, using a new class of bipartite probes that separate the luminescent and quenching functions into two coupled molecules. In particular, the STAQ (S uperresolution viaT ransientlyA ctivatedQ uencher) example we show herein employs the excited state absorbance (not ground state) of the partner to accept energy from and quench the luminescent dye. The result is that much less deactivation power is needed for superresolved (∼50 nm) imaging. Moreover, the TAQ partner excited by the "donut" beam is shown to quench several different visible dyes via the same mechanism, opening the door to easier multicolor imaging. We demonstrate three dyes sharing the same deactivation and show examples of superresolved multicolor images. We suggest STAQ will facilitate the growth of real‐time nanoscopy by reducing confounding photodamage within living cells while expanding the nanoscopist's palette. Microsc. Res. Tech. 78:343–355, 2015 . Published 2015. This article is a U.S. Government work and is in the public domain in the USA